The effect of Frayer's model on the acquisition of measurement concepts The evaluation of female teachers preparation institute students (Journal of the College of Basic Education, 2022)
The current research aims to find out (the effect of Fryer's model in acquiring the concepts of measurement and evaluationThe female teachers of the Teachers Preparation Institute) Therefore, the researcher put the following hypothesis- There is no statistically significant difference at (0560) between the mean scores of the group's studentsExperimental subjects who study measurement and evaluation according to the Frayer model and between the mean scoresThe students of the control group who study the same subject in the usual way. In an acquisition testDimensional concepts